2018
DOI: 10.1016/j.kint.2017.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury is a risk factor for subsequent proteinuria

Abstract: Acute kidney injury (AKI) is associated with subsequent chronic kidney disease (CKD), but the mechanism is unclear. To clarify this, we examined the association of AKI and new-onset or worsening proteinuria during the 12 months following hospitalization in a national retrospective cohort of United States Veterans hospitalized between 2004-2012. Patients with and without AKI were matched using baseline demographics, comorbidities, proteinuria, estimated glomerular filtration rate, blood pressure, angiotensin-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
46
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(52 citation statements)
references
References 76 publications
4
46
1
1
Order By: Relevance
“…Interestingly, patients with COVID-19 with elevated serum creatinine at admission exhibited a higher incidence of moderate proteinuria compared with those with normal serum creatinine (30.2% vs. 7.5%) (13). However, there is no evidence that this depends on a disturbed RAAS and actually relies on the proximal tubule cell response to injury, including the transient loss of polarity and cell death (7,54).…”
Section: Kidney Abnormalities Induced By Sars-cov-2: Potential Involvmentioning
confidence: 99%
“…Interestingly, patients with COVID-19 with elevated serum creatinine at admission exhibited a higher incidence of moderate proteinuria compared with those with normal serum creatinine (30.2% vs. 7.5%) (13). However, there is no evidence that this depends on a disturbed RAAS and actually relies on the proximal tubule cell response to injury, including the transient loss of polarity and cell death (7,54).…”
Section: Kidney Abnormalities Induced By Sars-cov-2: Potential Involvmentioning
confidence: 99%
“…However, the trajectory of AKD remains poorly elucidated.Cardiac surgery-associated AKI (CSA-AKI) is the second most common type of AKI (next to septic shock) and is associated with high in-hospital mortality 9,10 . In addition, CSA-AKI is proven to be a risk for CKD [11][12][13] . Among the characteristics of CSA-AKI are the various timings of occurrence (early or late phase after cardiac surgery) and the various clinical courses (transient or persistent renal dysfunction) due to the complex pathophysiology of CSA-AKI, which includes hemodynamic instability, mechanical stress such as cardiopulmonary bypass, inflammation, oxidative stress, neurohormonal factors, nephrotoxic agents and postoperative complications such as infections 14 .…”
mentioning
confidence: 99%
“…2 The phenotype of progression of CKD is usually described by two biomarkers: albuminuria and glomerular filtration rate (GFR). 8,9 With the rise of "omics" techniques, it has become evident that on a molecular level, CKD is even much more complex with multiple processes interacting. 3 Research typically focuses on specific factors and pathways that drive the progression of CKD with the ultimate aim to identify targets for intervention.…”
Section: Introductionmentioning
confidence: 99%
“…7 Research also identified acute kidney injury (AKI) as risk factor for the development of CKD, which also affects injury and repair mechanisms. 8,9 With the rise of "omics" techniques, it has become evident that on a molecular level, CKD is even much more complex with multiple processes interacting. 10 Furthermore, intrinsic protective pathways have been identified as well counterbalancing deleterious developments, and probably the rate of progression of CKD is ultimately determined by the balance between injury and repair.…”
mentioning
confidence: 99%